Curative effect of compound anisodine hydrobromide on the multifocal electroretinography waves in the early diabetic retinopathy - Li-Mei Gao (Guoji Yanke Zazhi, 2015)
AIM:To observe the clinical effect of compound anisodine hydrobromide acupoint injection therapy on the changes of the multifocal electroretinography(mfERG)waves in patients with diabetic retinopathy(DR). METHODS: In this prospective control study, 48 cases(48 eyes)with DR Ⅰ～Ⅱ period were divided into the injection group(24 eyes of 24 cases)and the control group(24 eyes of 24 cases). The cases in the control group were treated by conventional glucose-lowering therapeutic scheme. Those in the injection group were treated by compound anisodine hydrobromide acupoint injection 2mL and conventional glucose-lowering therapeutic scheme. The mfERG examination system(RETIscan 3.15 version, Roland, Germany)was applied. These waves of four quadrants of SN, IN, IT and ST, 6 rings and the sum responses from the mfERG examinations were observed and the average density of the sum response, the latent period and amplitude of P1 and N1 waves were analyzed by SPSS 13.0. RESULTS:The average density of the sum response of P1 and N1 waves in the injection group were 39.42±6.46 and 11.12±1.34nV/deg2 respectively, which were higher than those in the control group(28.50±3.73 and 6.33±1.14nV/deg2)(P1:t=6.230,P<0.01; N1: t=3.526, P<0.01). The average density of P1 in SN, IN, IT and ST quadrants in the injection group were 32.61±9.62, 32.31±7.94, 29.24±7.84 and 28.09±5.38nV/deg2 respectively, which were higher than those in the control group(P<0.05), while there were no statistic differences in the N1 waves between two groups. The average density of P1 in R1～R6 and N1 in R1～R3 in the injection group were 98.11±17.53, 73.95±17.20, 64.09±14.13, 49.43±10.08, 40.24±11.55, 36.86±6.43, 25.27±12.81, 21.31±6.76 and 14.86±5.06nV/deg2 respectively, which were higher than those in the control group(P<0.05). There was no significant difference on the average density of N1 in R4 ～ R6 between the two groups. The wave amplitude of P1 and N1 in IT and ST in the injection group were 1.37±0.35, 1.28±0.29, 0.31±0.05 and 0.30±0.10μV respectively, which were significantly higher than those in the control group(P<0.05)while there were no statistic differences in the P1 and N1 in SN and IN between two groups. CONCLUSION: The compound anisodine hydrobromide acupoint injection can improve the retinal function of DR in the early period.